Development and optimization of a novel controller for regenerative indirect evaporative cooler. (February 2019) - Chen, Yi; Yan, Huaxia; Min, Yunran
Abstract: The main characteristic of an indirect evaporative cooler (IEC) is the high dependency on ambient air conditions. To ensure stable indoor temperature and provide better thermal comfort, proper control strategy is essential. However, very limited studies report the controller used in IEC. In this paper, a novel control scheme named high-low (H-L) is proposed for regenerative indirect evaporative cooler (RIEC). Under H-L control scheme, the fans would be switched between high speed and low speed rather than completely turned off. The H-L control adopts the multi-speed technology, providing energy saving potential compared with conventional on-off control and overcome the complexity and costly of variable speed technology. The annual performance of RIEC was simulated under H-L control based on the RIEC model and dynamic indoor heat and mass balance model. The influence of low speed to high speed ratio (L/H) is discussed in order to propose an optimal L/H by considering both the thermal comfort and annual energy consumption. The results show that the H-L control can provide stable indoor temperature and satisfactory thermal comfort with Predicted Mean Vote (PMV) in the range of -0.5 to 0.5 for 76.2% of time. The optimal L/H is found to be 0.25 to 0.33 because of high thermal comfort provided and lowest energy consumption.